KARACHACHANAK DEPOSIT GAS CONDENSATE – PERSPECTIVE RAW MATERIAL FOR PETROCHEMISTRY - J.A. Tөruliev,; G.A. Orazova,; O. Yu. Panchenko,; D.ZH. Kalimanovа, (Academic Journal of Physical and Chemical Sciences, 2019)
Any condensate is obtained after a gaseous substance passes into a liquid due to a decrease in pressure or temperature. In the bowels of the earth there are not only gas, but also gas condensate deposits. When pressure and temperature decrease as a result of well drilling, gas condensate is formed - a mixture of liquid hydrocarbons separated from gas. Knowing amount sloppy cheese, delivered Karachaganak processing complex on consequent conversion in accordance with passport quality cheese with brought on contents faction before С19 and the other factor, on under development methods possible to calculate output base faction, used for reception of the goods products on full scheme to conversion cheese.